Performance and internationalization effects of the use of ICT in diversified companies - Omar Leoń; Juan Ignacio Igartua; Jaione Ganzarain (Small Business International Review (SBIR), 2018)
The relationship between Information and Communication Technologies (ICT) and business performance has been a topic of great importance for academics from different areas for several decades. In this sense, this study analyzes the impact of the use of ICT on the diversification strategy of small and medium enterprises (SMEs). From a sample of 95 companies in the Autonomous Community of the Basque Country, it is evident that diversified companies show a higher level of use of ICTs and that this resource affects positively the degree of international diversification and business performance. For the descriptive and correlational statistical analysis of the variables, the SPSS software version 21 was used.
Keywords: L25; M16; O33; 650; ICT; diversification; internationalization; performance; TIC; diversificacioń; internacionalizacioń; rendimiento